2007
DOI: 10.1101/gad.455407
|View full text |Cite
|
Sign up to set email alerts
|

Mismatch repair-dependent processing of methylation damage gives rise to persistent single-stranded gaps in newly replicated DNA

Abstract: [Keywords: DNA repair; DNA replication; methylating agents; mismatch repair; replication intermediates] Supplemental material is available at http://www.genesdev.org.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

17
156
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 159 publications
(174 citation statements)
references
References 42 publications
17
156
1
Order By: Relevance
“…The frequency of DSBs was quantitatively correlated with the frequency of apoptosis. This supports a model where MMR generates gaps in the DNA (Mojas et al, 2007) that block replication, which leads to DSBs at collapsed replication forks in the second cell cycle after treatment (Ochs and Kaina, 2000; for review see Kaina et al, 2007). Thus, DSBs are postulated to act as a downstream trigger of O 6 MeG-induced apoptosis.…”
Section: Discussionsupporting
confidence: 68%
“…The frequency of DSBs was quantitatively correlated with the frequency of apoptosis. This supports a model where MMR generates gaps in the DNA (Mojas et al, 2007) that block replication, which leads to DSBs at collapsed replication forks in the second cell cycle after treatment (Ochs and Kaina, 2000; for review see Kaina et al, 2007). Thus, DSBs are postulated to act as a downstream trigger of O 6 MeG-induced apoptosis.…”
Section: Discussionsupporting
confidence: 68%
“…In this scheme, homologous recombination performs a vital rescue function. The Jiricny lab has recently reported that treatment of mammalian cells with MNNG gives rise to MMR-dependent single-stranded gaps in newly replicated DNA (Mojas et al, 2007). These findings lend support for a "processing model" whereby MMR targets O 6 -meG mismatches but fails to complete excision repair leaving single-strand gaps that persist unrepaired into the second cell cycle where they cause replication fork collapse.…”
Section: Mmr and Dna Damage Signallingmentioning
confidence: 90%
“…Mutant human and Xenopus ATRIP proteins lacking an N-terminal region required for interaction with RPA and stable DNA binding nevertheless support ATR-mediated phosphorylation of Chk1 in response to DNA damage (Ball et al, 2005;Kim et al, 2005), and TopBP1 has been postulated to be a direct activator of ATR via specific protein-protein interactions (Kumagai et al, 2006). Understanding why O 6 -meG poses a block to gap repair in the MMR pathway is an important unanswered question as it does not appear to pose a block to replication per se (Mojas et al, 2007).…”
Section: Mmr and Dna Damage Signallingmentioning
confidence: 99%
“…Upon encountering a mismatch, the MSH heterodimers recruit another heterodimer composed of mutator L homolog 1 and postmeiotic segregation increased 2 (MLH1/PMS2) to coordinate downstream repair events (1,2). Exposure to certain DNA-damaging agents, such as methylating agents and the nucleotide analog 6-thioguanine (6TG), creates lesions in the genome that give rise to mismatches when replicated (3,4). The DNA MMR system recognizes these mismatches and induces cell death to remove them.…”
mentioning
confidence: 99%